SURVIVAL OF SAVINGS GROUP : MODEL OF SAVINGS GROUP MANAGEMENT FOR PRODUCTION BAN NONG MON, DON PHUT DISTRICT, SARABURI PROVINCE - Sanannaree, Nites; Buathet, Decha (Journal of Graduate MCU KhonKaen Campus, 2021)
The creation of agricultural cooperation of Thailand in 2511. Later in 2517, the Department of Community Development promoted and encouraged rural people to gather together to raise savings to set up a community fund in the form of " Production Savings Group” for helping oneself and help each other by borrowing for career investments. Savings Group of Ban Nong Mon Production occurred in accordance with the concept of the Department of Community Development due to the lack of funds for farming in the community. Over 34 years, it has been continuously developed to encourage members to have a stable livelihood. This research aimed to study a model of small savings group management and propose a model of sustainable savings group management in the future.The research method was a qualitative research.The group of key informants werethe chairpersons ,committee , 15 members.Data collected with in-depth interviews and observations with content-analysis. The results of the research were as follows: Savings groupfor the production of Baan Nongmon are small groups., They were grouped in a loosely network without permanentpersonnel but withVolunteer work. All investments were earned by members, no outside or government subsidies.There is a committee as the core in the management of each village. The monthly deposit is a minimum of 100 baht and not more than 500 baht per month.Application for a loan was only once a year,paying interest and principal together at the end of the year on the specified date. Management profits will be distributed to members 65% or 5-6% per share per year.Member benefits include childbirth, death, scholarship, medical treatment and help the disadvantaged and needy.The success and survival of the group depends on the committee's integrity, sacrifice, responsibility, contributing to its fellow members in a fair and equitable manner, thus building trust among its members.